The Behaviour of Intracellular Water in Yeast Cells Affected by Organic Solvents - V. M. Gun'ko; T. V. Krupska; V. M. Barvinchenko; V. V. Turov (Хімія, фізика та технологія поверхні)
Yeast Saccharomyces cerevisiae cells dry (containing approximately 7 wt.% of water) and partially rehydrated (10 wt.% addition of water) and with added organic solvents (10 wt.% or 2–3 g per gram of dry cells) nonpolar (C6H6, CCl4) or polar (CD3CN, (CH3)2CO, (CD3)2CO, (CH3)2SO, (CD3)2SO) were studied using 1H NMR spectroscopy with layer-by-layer freezing-out of bound and bulk liquids at 200–273 K, TG/DTA and FTIR spectroscopy methods. Nonpolar solvents displace a portion of water into narrower ‘pores’ in contrast to polar solvents which displace water into larger ‘mesopores’ in the intracellular space. This structural feature of intracellular water is accompanied by its energetic differentiation, and four types of intracellular water are found: weakly (chemical shift dH = 1–2 ppm) and strongly associated (dH = 3–5 ppm) waters which can be strongly (DG < -0.8 kJ/mol) or weakly (DG > -0.8 kJ/mol) bound to intracellular functionalities.